The baby has not come: obstructed labour - Nancy MacKeith; Wal Bichiok Wur (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2013)
This article is about how to recognize obstructed labour and deal with it in a way that preserves the life and health of mother and child. It is for midwives and others who work in maternity care and is based on our experiences in Yei, South Sudan. Obstructed labour means that the baby is too big to pass through the birth canal. It can be associated with prolonged labour. Prolonged labour can sometimes be treated, resulting in a normal delivery but a woman in true obstructed labour should be delivered by Caesarean section.